Controle de Célula de Produção de Tempo Real com DMIs - Cassol, Leandro Azevedo; Zorzo, Avelino Francisco (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2002: Anais do III Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2002.23397, 2002)
This paper presents the design of a controlling system for a production cell. The design uses an abstraction called Dependable Multiparty Interaction (DMI), which is used to enclose all interactions between the devices of the production cell. This paper also presents a short description of the production cell case study. The goal of the paper is to show that real time and fault tolerance requirements can be satisfied in a controlling software implemented with DMIs.